English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

m = (y2-y1)/(x2-x1)

4/3 = (3 - 7)/(r +2)
4(r+2) = 3(-4)
4r+8 = -12
4r = -20
r = -5

Check.

2006-12-14 18:40:09 · answer #1 · answered by Anonymous · 0 0

( y2 - y1 ) / ( x2 - x1 ) = m definition of the gradient
put in your values
( 3 - 7 ) / ( r -(-2) ) = 4/3
so
( 3 - 7 ) / ( r + 2 ) = 4/3
crossmultiply
3 x ( 3 - 7 ) = 4 x ( r + 2 )
expand brackets
9 - 21 = 8 + 4 x r
simplify
-12 - 8 = 4 x r
so r = -5

2006-12-14 15:41:26 · answer #2 · answered by Anonymous · 0 0

slope = (y1-y2)/(x1-x2) = 4/3
or (7-3)/(-2-r) = 4/3
or 4/(-2-r) = 4/3
or -2-r = 3
or r=-5

2006-12-14 15:48:28 · answer #3 · answered by sudhir49garg 2 · 0 0

since slope is equal to (y-y1)/(x-x2) you just plug in your values and solve for r.

2006-12-14 15:32:17 · answer #4 · answered by anime_girl90 2 · 0 0

fedest.com, questions and answers